Pharmacogenetics and Gender Association with Psychotic Episodes on Nortriptyline Lower Doses: Patient Cases. (20th July 2011) - Piatkov, Irina; Jones, Trudi
Abstract : The variation in individual responses to psychotropic drug treatment remains a critical problem in the management of psychotic disorders. Although most patients will experience remission, some patients may develop drug-induced adverse effects that may range from troublesome to life threatening. Antidepressants are freely prescribed by general practitioners, and there should be constant awareness in the medical community about possible serious side effects. We describe two cases of adverse drug reactions on low dosage treatment that led to extreme psychotic episodes as examples of the potential for dangerous side effects. The patients developed adverse reactions on the normal recommended dosage of nortriptyline, a tricyclics antidepressant (TCA). Both were females, with no history of antidepressant treatment, unsocial behaviour, nor any family history of psychosis, but both experienced severe psychiatric symptoms. Pharmacogenetic tests can easily be performed and interpreted according to the likelihood of adverse reactions and should be included in toxicity interpretation.